Protein Intake and Kidney Health: A Literature Review of Healthy Individuals, Athletes and CKD Patients - Skibicka, Katarzyna; Skibicki, Tomasz; Wesołowska, Weronika; Pietrzak, Jarosław (Journal of Education, Health and Sport, 2025)
Background: The relationship between dietary protein intake and kidney health varies across populations. High-protein diets are widely used by healthy individuals and athletes, while protein restriction is central to managing chronic kidney disease (CKD). Objective: To systematically review current evidence on the effects of dietary protein intake on kidney function in healthy individuals, athletes, and CKD patients. Methods: A systematic literature search was conducted in PubMed, Embase, and Cochrane databases from January 2000 to June 2025. Keywords included “protein intake,” “kidney function,” “CKD,” “high-protein diet,” “low-protein diet,” and MeSH terms. Studies were included if they were original research, meta-analyses, or RCTs examining protein intake and kidney outcomes. A total of 72 studies met the inclusion criteria. Quality of evidence was assessed using the GRADE framework. Results: High-protein diets in healthy adults result in adaptive, reversible hyperfiltration without long-term renal damage. Athletes show similar short-term safety, but prolonged high intake, especially from animal sources, may accelerate renal functional decline. CKD patients benefit from low- or very-low-protein diets, especially plant-based or ketoanalogue-supplemented regimens, which slow disease progression and improve metabolic outcomes. Evidence supports personalized dietary strategies based on population-specific needs. Conclusions: Protein intake impacts kidney health differently across populations. Personalized dietary guidance, including protein quantity and source considerations, is essential for maintaining renal function and preventing disease progression.